Russia‟s Interest In Pakistan And Its Implications On India - Chaliha, Dr. Farzia Yashmeen (The journal of contemporary issues in business and government, 2021)
The main objective of this paper is to examine the five prime reasons under which Russia had shifted its interest towards deepening their strategic relations with Pakistan keeping at stake its historic relations with India. Historically, both Soviet Union and Pakistan looked at each other either through the prism of U.S or India leaving little scope for independent foreign-policy making towards each other or even extending strategic manoeuvring. Currently, the orbit of their relations is undergoing rapid changes in the backdrop of the New Cold War. As such, besides, covering the historical background, the present study is therefore an attempt to analyse the growing geo-strategic interest of Russia in Pakistan and examine whether this reapproachment have any impact on Indo-Russian relations. In the process it also examines how their strategic synergy may alter the existing balance of power in South Asia and international peace.